EDUKASI INTERAKTIF DAN SKRINING KESEHATAN GINJAL PADA ANAK SEKOLAH DASAR - Sunarmi, Sunarmi; Septiana, Nita Tri; Izzati, Aisyah (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
Kidney health problems among children are increasingly prevalent, with many school-aged children even requiring hemodialysis. This condition is often caused by poor hydration behaviors, such as inadequate water intake, frequent consumption of packaged beverages, and improper urination habits. A lack of understanding about proper hydration practices for kidney health is a key factor contributing to these behaviors. This community service program aimed to improve children’s awareness and help them develop positive habits related to kidney health. The activity included interactive health education sessions using animated videos and urine color analysis screenings. The results showed a significant increase in students' understanding of kidney function (pre-test vs. post-test scores. This program highlights the importance of early health education, school-based interventions, and multisectoral collaboration in preventing kidney disease among children. These findings support the need for scalable and sustainable health promotion strategies in elementary schools to foster long-term kidney health awareness